Representasi Relasi Manusia Dan Alam Dalam Cerita Pendek “Asa Dan Hutan Kalimantan” Karya Yosimar Akbar - Aghist Muflihah Zahra; Melinda Febriani; Ian Wahyuni (FKIP, Universitas Palangka Raya, 2023)
This research uses a type of qualitative research using an ecocritical perspective. This research aims to identify forms of environmental wisdom and ecological criticism in the short story Asa and Hutan Kaimantan using Norman Fairclough's theory of critical discourse analysis, namely, identity, representation and relationships. The data in this research are several texts contained in short stories, while the data source in this research is the primary data source in the form of the short story